2005
DOI: 10.1097/01.ico.0000153099.96904.43
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination of Human Organ-Cultured Corneas

Abstract: The observation of microbial contaminations in a time close to the transplant (i.e., at the end of the preservation period and in the deswelling step) showed that a fast microbial tests during the deswelling procedure may prevent the grafting of a contaminated cornea. The appearance of bacteria in the deswelling medium despite a negative culture medium suggests that bacteria penetrate the corneal tissues during the culture to be subsequently extruded when the internal fluids move outward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…It has been suggested that stromal oedema may allow bacteria to enter the donor cornea. 27 Finally, in the New Zealand National Eye Bank report, 16 the mean death-to-preservation time was 15.2 h and it did not differ between corneas that were suitable for transplantation and those that were unsuitable.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that stromal oedema may allow bacteria to enter the donor cornea. 27 Finally, in the New Zealand National Eye Bank report, 16 the mean death-to-preservation time was 15.2 h and it did not differ between corneas that were suitable for transplantation and those that were unsuitable.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, some latent infections may be inhibited by the fresh antibiotic dose in the deswelling medium, but others may be boosted by the fresh nutrient supply or activated by the deswelling process itself [35]. On the other hand, it is known that Dextran 500 contained in the deswelling medium displays toxicity [5,17,23,25,36], and that the deswelling duration should be kept to the necessary minimum.…”
Section: Discussionmentioning
confidence: 99%
“…Zanetti et al used a combination of classic and automated test systems to assess their contamination rates [35]. In 1,694 corneas they saw 119 (7.02%) primary contaminations.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] The Hamburg eye bank found 4.7% fungal and 2.6% bacterial contaminants in 4546 tested cultures. 9 In contrast, the Besançon group reported 1.1% fungal and 4.6% bacterial contamination in 1156 tested storage media.…”
Section: Discussionmentioning
confidence: 99%